Stevens-Johnson syndrome and toxic epidermal necrolysis in childhood-onset systemic lupus erythematosus patients: a multicenter study - Sakamoto, A. P.; Silva, C. A.; Saad-Magalhaes, C. [UNESP]; Alencar, A. N.; Pereira, R. M. R.; Kozu, K.; Barbosa, C. M. P. L.; Terreri, M. T. (Publisaude-edicoes Medicas Lda, 2017)
Objective: To assess Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) in a large population of childhood-onset systemic lupus erythematosus (cSLE) patients. Methods: Multicenter study including 852 cSLE patients followed in Pediatric Rheumatology centers in Sao Paulo, Brazil. SJS was defined as epidermal detachment below 10% of body surface area (BSA), overlap SJS-TEN 10-30% and TEN greater than 30% of BSA. Results: SJS and TEN were observed in 5/852 (0.6%) cSLE female patients, three patients were classified as SJS and two patients were classified as overlap SJS-TEN; TEN was not observed. The mean duration of SJS and overlap SJS-TEN was 15 days (range 7-22) and antibio tics induced four cases. Regarding extra-cutaneous manifestations, hepatomegaly was observed in two cSLE patients, nephritis in two and neuropsychiatric involvement and conjunctivitis were observed respectively in one patient. Hematological involvement included lymphopenia in four, leucopenia in three and thrombocytopenia in two patients. The mean SLEDAI-2K score was 14.8 (range 6-30). Laboratory analysis showed low C3, C4 and/or CH50 in two patients and the presence of anti-dsDNA autoantibody in two patients. One patient had lupus anticoagulant and another one had anticardiolipin IgG. All patients were treated with steroids and four needed additional treatment such as intravenous immunoglobulin in two patients, hydroxychloroquine and azathioprine in two and intravenous cyclophosphamide in one patient. Sepsis was observed in three cSLE patients. Two patients required intensive care and death was observed in one patient. Conclusion: Our study identified SJS and overlap SJS-TEN as rare manifestations of active cSLE associated with severe multisystemic disease, with potentially lethal outcome.
Keywords: Stevens-Johnson syndrome; Toxic epidermal necrolysis; Childhood-onset systemic lupus erythematosus; Systemic lupus erythematosus; Childhood